Minimal decision rules based on the Apriori algorithm - Fernández, Maria C.; Menasalvas, Ernestina; Marbán, Óskar; Pena, José M.; Millán, Socorro (Zielona Góra: Uniwersytet Zielonogórski)
Based on rough set theory many algorithms for rules extraction from data have been proposed. Decision rules can be obtained directly from a database. Some condition values may be unnecessary in a decision rule produced directly from the database. Such values can then be eliminated to create a more comprehensible (minimal) rule.
Keywords: rough sets; rough dependencies; association rules; Apriori algorithm; minimal decision rules